1989
DOI: 10.1002/cne.902890408
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of β‐nerve growth factor receptors in the human basal forebrain

Abstract: The distribution of neurons expressing the receptor for beta-nerve growth factor has been examined immunohistochemically in serial coronal sections of basal forebrain from aged normal human subjects. Neurons expressing the receptor were observed in the nucleus of the diagonal band of Broca and in the anterior, the intermediate, and the posterior portions of the nucleus basalis of Meynert. Neurons could also be seen in the medial septal nucleus and embedded in myelinated fibre tracts such as those of the extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 66 publications
4
15
0
Order By: Relevance
“…That concept of a neuronal shell enclosing the globus pallidus was extensively confirmed in subsequent studies of the magnocellular cholinergic basal forebrain system in both human and monkey, by means of various markers of these neurons such as AChE, choline-acetyltransferase, nerve growth factor and nerve growth factor receptors (trk1, p75). Displaced cholinergic neurons (usually interpreted as belonging to the Ch4 group or basal nucleus of Meynert) were documented within the internal and external capsule, anterior commissure and medullary laminae separating two segments of the globus pallidus as well as the globus pallidus from the putamen (Mesulam et al 1983;Mesulam & Mufson, 1984;Satoh & Fibiger, 1985;Kordower et al 1988Kordower et al , 1989Kordower et al , 1994Mesulam & Geula, 1988;Allen et al 1989;Mufson et al 1989). Although there is no clear evidence that these cholinergic neurons also synthesize nitric oxide, NADPH-d-positive fibres were noted in the human external capsule (Ellison et al 1987) and NOS-immunoreactive neurons (Satoh et al 1995), and neuropeptide Y-immunoreactive neurons were found in the monkey external capsule and medullary laminae surrounding human globus pallidus (Lehé ricy et al 1993).…”
Section: Deep Interstitial Neurons Surrounding the Globus Pallidus Anmentioning
confidence: 99%
“…That concept of a neuronal shell enclosing the globus pallidus was extensively confirmed in subsequent studies of the magnocellular cholinergic basal forebrain system in both human and monkey, by means of various markers of these neurons such as AChE, choline-acetyltransferase, nerve growth factor and nerve growth factor receptors (trk1, p75). Displaced cholinergic neurons (usually interpreted as belonging to the Ch4 group or basal nucleus of Meynert) were documented within the internal and external capsule, anterior commissure and medullary laminae separating two segments of the globus pallidus as well as the globus pallidus from the putamen (Mesulam et al 1983;Mesulam & Mufson, 1984;Satoh & Fibiger, 1985;Kordower et al 1988Kordower et al , 1989Kordower et al , 1994Mesulam & Geula, 1988;Allen et al 1989;Mufson et al 1989). Although there is no clear evidence that these cholinergic neurons also synthesize nitric oxide, NADPH-d-positive fibres were noted in the human external capsule (Ellison et al 1987) and NOS-immunoreactive neurons (Satoh et al 1995), and neuropeptide Y-immunoreactive neurons were found in the monkey external capsule and medullary laminae surrounding human globus pallidus (Lehé ricy et al 1993).…”
Section: Deep Interstitial Neurons Surrounding the Globus Pallidus Anmentioning
confidence: 99%
“…The majority of magnocellular neurons in these nuclei are P-NGF receptor positive [24], and there appears to be a high degree of colocalization between ChAT-positive and (3-NGF-receptor-immunoreactive neurons [19]. In situ hybridization using a radiolabelled cDNA probe to the human p-NGF receptor has confirmed magnocel lular neurons as the site of synthesis of p-NGF receptors [24,25].…”
Section: Introductionmentioning
confidence: 98%
“…This monoclonal antibody binds to the human low-affinity P-NGF recep tor and blocks the binding of [l2SI]-p-NGF to SK-MEL-13 mela noma cells {36]. Immunohistochemical staining was carried out as described previously [24]. Briefly, coronal sections (30 pm thick) were cut on a freezing microtome and collected in triplicate, free floating, every 300 pm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NGF-receptors are expressed on the cholinergic neurons of the basal forebrain and can be demonstrated on their dendrites in the target areas (Allen et al 1989). This suggests that NGF is produced by these target areas so as to be retrogradely transported to the cholinergic cell bodies in the basal forebrain area.…”
mentioning
confidence: 99%